1977
DOI: 10.1111/j.1476-5381.1977.tb06976.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reserpine‐induced Supersensitivity of the Positive Inotropic and Chronotropic Responses to Isoprenaline and Salbutamol in Guinea‐pig Isolated Atria

Abstract: I Dose-response curves for the positive inotropic and chronotropic responses to isoprenaline were obtained in atria from untreated guinea-pigs and those receiving various reserpine pretreatments. 2 Tension responses were unaffected, whereas rate responses were depressed by the lowest dose of reserpine (0.05 mg/kg i.p. at 24 hours). 3 With larger 24 h doses and a 3 day pretreatment, the rate and tension dose-response curves were progressively displaced to the left, indicating supersensitivity which was greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

1977
1977
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…Several reports have suggested that the supersensitivity phenomenon is specific, i.e. demonstrable only with fi-adrenoceptor agonists (Broadley & Lumley, 1977;Haw-thorn & Broadley, 1984). Indeed, several studies have demonstrated increased fi-adrenoceptor density after chronic reserpine treatment (Tenner et al, 1982;Latifpour & McNeill, 1984;Chess-Williams et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have suggested that the supersensitivity phenomenon is specific, i.e. demonstrable only with fi-adrenoceptor agonists (Broadley & Lumley, 1977;Haw-thorn & Broadley, 1984). Indeed, several studies have demonstrated increased fi-adrenoceptor density after chronic reserpine treatment (Tenner et al, 1982;Latifpour & McNeill, 1984;Chess-Williams et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Some report an increase ( 19) and the others report no change (2,12) in the IT in the atria from reserpinized animals. No significant changes in maximal developed force was reported following reserpinization (6,11,12,20).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of norepinephrine from the nerve endings alone is not sufficient to induce supersensitivity since the development of supersensitiv ity and the degree of norepinephrine depletion are not directly related (7,15). Those who observed specificity to catecholamines have suggested a certain change at the adrenergic receptor site, possibly an increase in the number of available receptors (2,9) or an increased efficacy of the receptor (2). Several workers (9,12,24) have suggersted that the mechanism of non selective supersensitivity lies beyond the receptor, such as an alteration in membrane permeability or in the contractile mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations